Shaping Strategic Action Through the Rhetorical Construction and Exploitation of Ambiguity - Sillince, John; Jarzabkowski, Paula; Shaw, Duncan (Organization Science, 2012)
This paper extends existing understandings of how actors' constructions of ambiguity shape the emergent process of strategic action. We theoretically elaborate the role of rhetoric in exploiting strategic ambiguity, based on analysis of a longitudinal case study of an internationalization strategy within a business school. Our data show that actors use rhetoric to construct three types of strategic ambiguity: protective ambiguity that appeals to common values in order to protect particular interests, invitational ambiguity that appeals to common values in order to invite participation in particular actions, and adaptive ambiguity that enables the temporary adoption of specific values in order to appeal to a particular audience at one point in time. These rhetorical constructions of ambiguity follow a processual pattern that shapes the emergent process of strategic action. Our findings show that (1) the strategic actions that emerge are shaped by the way actors construct and exploit ambiguity, (2) the ambiguity intrinsic to the action is analytically distinct from ambiguity that is constructed and exploited by actors, and (3) ambiguity construction shifts over time to accommodate the emerging pattern of actions.